Penerapan prinsip Biofilik pada Interior Kamar Deluxe Hotel Resort Grand Natura di Sabang - kansa amirah ulfah (Jurnal Ilmiah Mahasiswa Arsitektur dan Perencanaan, 2018)
More than half of the world's population now lives in urban areas, each year the level of stress in urban areas continues to increase, higher levels of stress can affect the mental health of urban residents. One of the causes of stress in cities is because the population stays too long in unnatural manmade environments. Basically humans come from nature and have a need for nature in their lives, so to reduce stress levels in urban populations, residents must balance life in urban and natural environments. One solution to this is to go on vacation to Resort Hotels located close to nature. The Grand Natura Resort Hotel in Sabang is located in Paya Village, Sukajaya District, Sabang, Indonesia. Located in a mountainous area far from urban areas. This Resort Hotel carries the theme "Connect with Nature" with a Biophilic style approach. The principle of Biophilic design was coined by Steven Kellert with 6 design elements and 72 attributes of application which aim to include nature in building design. One part of the design most used by users is a hotel room. Therefore the interior of hotel rooms is made by applying the Biophilic principle. The interior of the hotel rooms is designed directly with the opening of the view towards the tropical forest and incorporating natural light, indirectly applied with the presence of tree twigs and tree branch patterns on the carpet, symbolically with natural wood colors and the shape of lamp furniture and round tables in bedside.